Corporate Governance and Financial Distress: Empirical Evidence from listed Consumer Services Firms in Sri Lanka - Balagobei, S.; Keerthana, G. (Global Academy of Training & Research (GATR) Enterprise, 2022)
Objective - COVID – 19 has created unique and very profound challenges for almost all listed firms in Sri Lanka. The purpose of the study is to examine the influence of corporate governance practices on the financial distress status of listed companies in the consumer services sector in Sri Lanka. Methodology/Technique – To assess the level of corporate governance, the current study constructs six dimensions of corporate governance, such as board size, board composition, CEO duality, board meeting, director ownership, and audit committee size. The Altman Z-score is used as a proxy for financial distress and measures it inversely. The bigger the Z-score indicates the smaller the risk of financial distress. Using 108 individual observations of consumer services firms listed on the Colombo Stock Exchange for the period of 2019 to 2021 and employing the fixed effects model, the effect of corporate governance practices on financial distress is evaluated. Findings - The results from panel data regression analysis reveal that firms having a large number of directors on the board have a low likelihood of financial distress of listed consumer services companies in Sri Lanka. Furthermore, when a chief executive officer serves as the chairman of the board at a company, the more likely it is that the company will experience financial distress. The current study also provides evidence that firm-specific characteristics, such as firm size, leverage, and profitability, could be useful in determining the likelihood of financial distress. Novelty - This study extends the existing literature by investigating the association between corporate governance practices and financial distress in listed companies in the emerging markets during the period of the COVID 19 pandemic.
Keywords: Board size; CEO duality; Corporate governance; Financial distress